Abundant expression of parathyroid hormone-related protein in human amnion and its association with labor. - Ferguson, J E (1992)
In animal models, parathyroid hormone-related protein (PTHrP) increases placental calcium transport and inhibits contraction of uterine smooth muscle. The present studies were undertaken to characterize the expression of PTHrP in human uteroplacental tissues. PTHrP mRNA was identified by Northern analysis as a single species (approximately 1.8 kilobases) in human amnion, chorion, placenta, decidua, and myometrium. The most abundant signal was seen in amnion, where it was 10-400 times that in the other uteroplacental tissues. PTHrP mRNA abundance was decreased in amnion (but not in the other tissues) following the onset of labor (P less than 0.001). PTHrP mRNA in amnion appeared to be translated to a bioactive peptide, as PTHrP bioactivity and immunoreactive PTHrP in amnion correlated closely with PTHrP mRNA content (r = 0.86 and 0.95, respectively; P less than 0.05 and P less than 0.01). Amniotic fluid contained PTHrP, 21 +/- 6 pmol/liter (n = 10) at 16 weeks and 41 +/- 9 pmol/liter (n = 7) at 38 weeks (P = 0.05). These concentrations equaled or exceeded those found in plasma of patients with hypercalcemia secondary to PTHrP. After rupture of the fetal membranes, PTHrP mRNA in amnion was decreased by 78% (P less than 0.0001). This decrease appeared to be specific for PTHrP mRNA, as glyceraldehyde-3-phosphate dehydrogenase mRNA was unchanged following rupture of membranes. Like PTHrP mRNA, PTHrP bioactivity and immunoreactive PTHrP in amnion decreased significantly following rupture of membranes (P less than 0.03 and P less than 0.01, respectively). Since PTHrP is a potent antagonist of uterine muscle contraction, the decrease of PTHrP following rupture of the fetal membranes may play a key role in the onset of labor.